Quo vadis' How to measure the quality of local and regional development processes' - Martin Strele; Manfred Walser (European Regional Science Association (ERSA), 2003)
Today most activities which seem to be sound, cosy and helpful - or sometimes simply useful - are called 'sustainable'. Of course the requirements for measuring sustainability increased rapidly. Many different systems of indicators and conflicting opinions about the adequate approach characterise the present situation. Nevertheless we add another system with an specific approach to evaluate processes of local and regional development. In our opinion it is able notably to refer to the quality of the concept of sustainability. The basic system is threefold and bears analogy to the model of total quality management. We distinguish between: · The assessment of projects with respect to material, procedural and ethical implications. The conceptual framework is translated into an evaluation checklist to systematise the discussion of the character and general impact of a given project or programme. The methodology of this section has been presented at the 39th ERSA Congress 1999 in Dublin even and until now has been applied in different fields. · The assessment of development processes in terms of organisation, methodology, contents and legal demands. This section will be the main part of our presentation. · And the assessment of the state of the region which actually is a 'work in progress'. It will combine elements of 'top-down indicators, deduced from the international and national discussion of the CSD-scheme, with elements of regional specific indicators based on a bottom-up approach which defines regional specific goals of development according to a transdisciplinary approach of how to experience the local and regional space. Our methodology is based on self-evaluation and it can come into operation at an early stage accompanying the activities over the whole life cycle. The assessment of development processes is to be done from the local and regional actors for themselves, accompanied by scientific experts. It depends on four principles: · The people concerned are the experts. They get involved in learning processes. · The focus of the assessment is on credibility and transparency. · Development processes need a minimum of quality. The standard is fixed. · The quality management can be used in a flexible way to allow the assessment of different processes according to the communities main focus. The whole project of quality management is closely coupled with the regional Agenda 21 in the Lake of Constance- region as it has been shown eat the 40th ERSA Congress 2000 in Barcelona. Together with the network of 13 regional contact points in Switzerland, Austria, Germany and the Principality of Liechtenstein the different sections has been discussed and field-tested. 437 words Key words: sustainability, Agenda 21, quality management, development processes, transdisciplinarity
Keywords: 330